High Utility Pattern Mining: A Survey on Current and Possible Areas of Applications - Bokir, Abdullah; Narasimha, Vb (Review of Information Engineering and Applications, 2022)
High Utility Pattern Mining (HUPM) has a wide range of applications, including making recommendations, detecting outliers, analyzing customer behaviors, and solving a wide range of other problems. In fact, unlike other important data mining tasks such as outlier analysis and classification, high utility pattern mining can be used as an intermediary tool for providing pattern-centered insights for other data mining tasks. In this paper, we look at a wide range of different applications of high utility pattern mining that are available in the literature. We gathered the literature review papers from different resources based on the keywords related to the applications of high utility pattern mining. Then we classified the existing research papers into different categories according to the domain application, then we summarize the proposed method of each paper and the datasets used for the evaluation process. Rather than providing a full discussion of every possible application, the objective of this paper is to give readers an overview of what is feasible when high utility pattern mining approaches are used. This paper can help researchers to apply the techniques of high utility pattern mining to solve real-time problems and it can help to explore other possible domains to apply high utility pattern mining techniques by proposing new methods and evaluating them accordingly.